Gagging: A problem in prosthetic dentistry and its medical treatment - Nagham H Kassab; Maha T Al-Saffar (University of Mosul, College of Dentistry, 2005)
Abstract This study was designed to diagnose and treat patients having gagging reflex whom need prosthetic treatment; patients in this study were wearing denture or received new one; those attending Prosthodontic Department/ College of Dentistry/ University of Mosul. The sample of this study was 243 patients consisting of 167 males and 76 females and their ages ranged between 22- 79 years old. All of them had either single upper, partial or complete denture excluding from this study all patients who did not have denture before, because this study directed toward prosthetic patients only. A sample, which consists of 243 patients, was divided into two main groups according to their response to gag reflex. The first one represented the control group which consisted of 200 patients, those did not have gagging reflex problem while the second group which represented those patients who they suffer from gagging problem when they are wearing or during denture insertion and consisted of 43 patients: Each one of them subdivided furthermore into subgroups according to patient's medical health status and sex. The second group (gagging patient) subdivided furthermore into 3 subgroups according to severity of gag reflex in which according to that, treatment plan had been made and it consisted of psychological treatment only for patients with mild and moderate gagging and medical and psychological treatment for patients with severe gagging reflex which include metoclopromide and valium 2. The result of this study demonstrated that those patients with severe gagging reflex problem reflect difficulties during prosthetic treatment which required medical and psychological treatment, which include reassurance of patient with explanation of steps of prosthetic treatment plan to reduce fear and anxiety before any prosthesis construction and the response of those patients to medical treatment was approximately 58.3% to this treatment and it was concluded that any type of prosthetic treatment in patients with gagging reflex required medical and psychological treatment plan.